PENERAPAN TEORI BELAJAR HUMANISTIK : STUDI KASUS IMPLEMENTASI METODE KERJA KELOMPOK PADA MATA PELAJARAN IPAS PADA MATERI BENTANG ALAM DAN KETERKAITANNYA DENGAN PROFESI MASYARAKAT DI KELAS IV SD NEGERI 012 KUARO - Lina, Mau (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the limited student engagement and low motivation observed in Grade IV at SD Negeri 012 Kuaro, where Science and Social Studies (IPAS) instruction remains teacher-centered. The research aims to explore the implementation of humanistic learning theory through group work as an alternative approach to enhance student participation and learning outcomes, particularly in the topic “Landforms and Their Relationship to Community Professions.” Employing a qualitative case study design, data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which involves data reduction, data display, and conclusion drawing. The findings indicate that the integration of group work based on humanistic principles fosters a more inclusive and student-centered learning environment. This approach enhances students’ self-confidence, collaboration, and intrinsic motivation. The teacher’s role shifted to that of a facilitator, supporting students’ emotional and social needs while promoting active participation and critical thinking. The study concludes that applying humanistic learning theory through cooperative learning strategies effectively creates meaningful learning experiences and aligns with the principles of the Merdeka Curriculum. These findings support the broader adoption of humanistic approaches to enrich IPAS instruction in elementary education.